Relevance of ACSL3-mediated ACS activity and ACSL3 localization in anabolic and catabolic lipid droplet metabolism - Sander, Simone (2019)
Abstract: Lipid droplets (LD) are intracellular storage organelles that are found in most of all cell types and play an important role in the pathology of various human diseases like diabetes type II, cardiomyopathy and atherosclerosis. The core of the LD consists of different neutral lipids, mainly triglycerides and cholesteryl esters. This hydrophobic core is surrounded by a phospholipid monolayer embedding specific proteins and enzymes. One of these enzymes is the long chain acyl-CoA synthetase 3 (ACSL3) that belongs to the family of acyl-CoA synthetases (ACS). Proteins of the ACS family catalyze the esterification of fatty acids with coenzyme A, which is an essential prerequisite for further metabolism. Among all ACS family members, ACSL3 is the only ACS enzyme that is consistently found on LD. ACSL3 is characterized by a dual localization on LD and the endoplasmic reticulum (ER). It translocates from the ER to the LD upon fatty acid supplementation and is already present on nascent LD. Based on the current data, ACSL3 localization on LD and the ACS activity mediated by ACSL3 is presumed to be biologically relevant. This work investigated the relevance of ACSL3-mediated ACS activity and ACSL3 localization in anabolic and catabolic lipid metabolism. The main approach was based on the depletion of ACSL3 in COS-7 cells by RNA interference or CRISPR/Cas9 knockout. ACSL3-knockout cells were transduced with genetically modified enzyme variants and lipid metabolism was investigated. A mutated ACSL3 variant lacking ACS activity was applied to identify potential ACSL3 functions independent of ACS activity. An ACSL3 variant localized to the ER but excluded from the LD was supposed to elucidate the importance of ACSL3 localization on LD. Experimental approaches included radiolabelling and quantification of intracellular lipid species by 14C-oleic acid and 14C-acetate, quantification of newly synthesized LD in starved cells and intracellular triglyceride measurement during basal lipolysis. Molar quantification of ACSL3 in A431 cells was carried out to calculate the metabolic capacity of LD-associated ACSL3 for triglyceride synthesis. ACSL3-knockout reduced ACS activity by 93 % indicating that ACSL3 is the dominant ACS family member in COS-7 cells. Incorporation of 14C-oleic acid was significantly decreased by 33 % in the ACSL3-knockout cells compared to wildtype COS-7 cells. Triglyceride synthesis was markedly reduced by approximately 50 % and LD biogenesis was decreased by 65 % in the ACSL3-knockout cells compared to wildtype COS-7 cells. The basal lipolytic rate was increased in the ACSL3-knockout cells resulting in intracellular triglyceride levels that were 46 % lower than the triglyceride levels measured in the control cells after 6 h of starvation. Cells expressing the ACSL3 variant lacking ACS activity were slightly reduced in basal lipolysis and thus exhibited triglyceride levels elevated by 24 % compared to the ACSL3-knockout cells after 6 h of starvation. Cells expressing only ER-localized ACSL3 were increased in triglyceride synthesis, but decreased in LD biogenesis by 54 % compared to cells expressing also LD-associated ACSL3. Model calculations in A431 cells estimated that local triglyceride synthesis on LD accounted to 3.3 % of total cellular triglyceride synthesis. In conclusion, this study revealed that ACSL3 is essential for triglyceride synthesis and LD biogenesis by activating fatty acids and delivering them to enzymes involved in lipid synthesis. However, the metabolic capacity of LD-associated ACSL3 is too low to significantly contribute to LD growth. Thus, LD expansion is probably dependent on lipid transfer from the ER to the LD. Moreover, ACSL3 decreases lipolysis maybe by re-esterification of fatty acids deliberated during lipolysis but also possibly by recruitment of antilipolytic proteins to the LD. ER-localized ACSL3 is superior in triglyceride synthesis probably due to the proximity of lipogenic enzymes harboured in the ER membrane. Furthermore, ACSL3 localization appears to be important for LD formation. ACSL3 is an important key player involved in lipid metabolism. Future studies of its underlying functional mechanism are promising to advance the understanding of diseases associated with lipid metabolism and to develop new therapeutic strategies.
Keywords: Hochschulschrift